Falsafah Liberalisme di Malaysia: Satu Sorotan Awal : Liberalism Philosophy in Malaysia: A Preliminary Highlights - Mohamad Kamil, Ibrahim Majdi; Mohd Khambali@Hambali, Khadijah; Wan Ramli, Wan Adli (Online Journal of Research in Islamic Studies, 2022)
This article focuses on the evolution and development of liberalism especially in Malaysia since being brought by western colonizers till form social movements in Malaysia preliminary. The philosophy of liberalism in Malaysia is not a newly thought issue, but one that has existed among Malaysian Muslim community for a long time. Throughout the history, the liberalism ideology has evolved among the people of Malaysia since it was first brought in, it is known as liberal Islamic movements. In the modern times, Liberalism’s advocates have increasingly and rapidly embraced the ideology of liberalism, especially through the liberal Islamic movement and in the name of human rights. Although liberalism has been part of the society in the areas of life such as economy, politics, culture, law and administration in Malaysia, the development and dissemination of the liberalism ideology can lead to a threat in ‘aqidah (faith) especially among Muslims today in Malaysia.